Implementation of the PQ4R learning method to build disposition and enhance student critical thinking skills - Wulan Purnamasari; AA Sukarso; Kusmiyati Kusmiyati; I Wayan Merta (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to determine the role of the PQ4R learning method in building critical dispositions and improving students' critical thinking skills on the subject of the human reproductive system. This research was conducted using the technique pretest-posttest control group design. Data were collected with instruments in the form of critical disposition questionnaires and tests of critical thinking skills. The subjects of this study were 69 students divided into two classes, which were taken from the population of course XI IPS SMAN 7 Mataram using the purposive sampling technique—the data analysis using t-test and testN-gain. The research results show an increase in critical dispositions and critical thinking skills in the experimental class compared to the control class, each of which is indicated by the t-test results of 0.000 <0.05. Changes (increases) in students' critical dispositions for the experimental class belonged to the medium category, and the control class belonged to the low category. The improvement of critical thinking skills in the experimental class is in the high category, and in the control class, it is in the low category. This research concludes that the PQ4R learning method can build students' dispositions and critical thinking skills. Recommendations from this study: The PQ4R learning method is suggested by teachers as an alternative effort to improve students' critical thinking skills.